Your Cheating Cognitions: Young Women's Responses to Television Messages about Infidelity. Issue 2 (3rd March 2020) - Alexopoulos, Cassandra; Taylor, Laramie D.
Abstract : The current study examined how exposure to a depiction of sexual infidelity on television influenced women's responses to hypothetical infidelity. In addition, we examined three individual factors as moderators for these effects: experience with infidelity, infidelity concern, and loyalty concern. In a laboratory experiment, young women were exposed to a media narrative featuring either a romantic relationship, the same relationship but with one partner engaging in sex outside the relationship, or a control narrative before completing measures of reactions to hypothetical relationship transgressions. Results indicated that women who had a cheating partner and exhibited high levels of concern about infidelity reported a lower tolerance for infidelity following exposure to a television narrative featuring infidelity.